Assessment of the Influence of Walkability Factors on Corridor Via VIII Febbraio and Via Roma in Padova, Italy - Windu Laskara, Gede; Devina Hermawan, Michella (Universitas Ibn Khaldun Bogor, 2022)
Planning and designing for walking are essential to encourage healthy public life, develop sustainable neighborhoods, and improve social life and the economy. In order to promote neighborhood sustainability and public life, this article outlines the elements and factors that lead to more excellent urban walkability. For the research to measure the sense of walkability, a case study was undertaken in the city center of Padova to evaluate pedestrian walking behavior in the city's most historical corridor. The existing Via VIII Febbraio & Via Roma, two famous pedestrian-dedicated streets which make up a long corridor in the heart of Padova, were chosen as the key case study for they serve an important role in the area, hosting many historic buildings in close proximity. The findings showed that the most critical elements influencing pedestrians' perceptions of walkability in the area were linked to convenience and visual attractiveness.